Restricted Size Ramsey Number for Matching versus Tree and Triangle Unicyclic Graphs of Order Six - Elda Safitri; Peter John; Denny Riama Silaban (LPPM Institut Teknologi Sepuluh Nopember, 2022)
Let F, G, and H be simple graphs. The graph F arrows (G, H) if for any red-blue coloring on the edge of F, we find either a red-colored graph G or a blue-colored graph H in F. The Ramsey number r(G,H) is the smallest positive integer r such that a complete graph Kr arrows (G,H). The restricted size Ramsey number r*(G,H) is the smallest positive integer r* such that there is a graph F, of order r(G,H) and with the size r*, satisfying F arrows (G,H). In this paper we give the restricted size Ramsey number for a matching of two edges versus tree and triangle unicyclic graphs of order six.